Osteocytes and the pathogenesis of hypophosphatemic rickets - Yamazaki, Miwa; Michigami, Toshimi (Frontiers in Endocrinology, 2022)
Phosphorus is a constituent of hydroxyapatite, and its chronic deficiency leads to impaired skeletal mineralization. Fibroblast growth factor 23 (FGF23), which plays a central role in phosphate homeostasis, is mainly produced by osteocytes and reduces serum phosphate levels by increasing the excretion of inorganic phosphate (Pi) and suppressing the production of 1,25-dihydroxyvitamin D in the kidneys. Osteocytes are terminally differentiated cells of osteoblastic lineage and are embedded in the mineralized bone matrix. In addition to FGF23, osteocytes express multiple genes that are responsible for hereditary hypophosphatemic rickets, which include phosphate-regulating gene homologous to endopeptidase on X chromosome (PHEX), dentin matrix protein 1 (DMP1), and family with sequence similarity 20, member C (FAM20C). Since inactivating mutations in PHEX, DMP1, and FAM20C cause the overproduction of FGF23, these molecules may function as local negative regulators of FGF23 in osteocytes. Mouse studies have suggested that enhanced FGF receptor (FGFR) signaling is involved in the overproduction of FGF23 in PHEX-deficient X-linked hypophosphatemic rickets (XLH) and DMP1-deficient autosomal recessive hypophosphatemic rickets type 1. Since FGFR is involved in the transduction of signals evoked by extracellular Pi, Pi sensing in osteocytes may be abnormal in these diseases. Serum levels of sclerostin, an inhibitor Wnt/-catenin signaling secreted by osteocytes, are increased in XLH patients, and mouse studies have suggested the potential of inhibiting sclerostin as a new therapeutic option for the disease. The elucidation of complex abnormalities in the osteocytes of FGF23-related hypophosphatemic diseases will provide a more detailed understanding of their pathogenesis and more effective treatments.